Effects of antiplatelet therapy on platelet extracellular vesicle release and procoagulant activity in health and in cardiovascular disease. (16th November 2016) - Connor, David E.; Ly, Ken; Aslam, Anoosha; Boland, John; Low, Joyce; Jarvis, Susan; Muller, David W.; Joseph, Joanne E
Abstract: Dual antiplatelet therapy with aspirin and clopidogrel is commonly used to prevent recurrent ischemic events in patients with cardiovascular disease. Whilst their effects on platelet reactivity are well documented, it is unclear, however, whether antiplatelet therapy inhibits platelet extracellular vesicle (EV) release. The aim of this study was to investigate the effects of antiplatelet therapy on platelet EV formation and procoagulant activity. Blood samples from 10 healthy controls not receiving antiplatelet therapy were incubated in vitro with aspirin or a P2Y12 inhibitor (MeSAMP). Blood samples from 50 patients receiving long-term dual antiplatelet therapy and undergoing coronary angiography were also studied. Platelet reactivity was assessed by Multiplate™ impedance aggregometry. Platelet EV formation and procoagulant activity of pretreated and untreated blood samples in response to arachidonic acid (AA), adenosine diphosphate (ADP), ADP+PGE1, and thrombin receptor-activating peptide (TRAP) stimulation were assessed by flow cytometry and Procoag-PL assays, respectively. Incubation of normal platelets with aspirin significantly inhibited AA-induced platelet reactivity, EV formation, and procoagulant activity, whilst MeSAMP significantly inhibited platelet reactivity and EV formation in response to AA, ADP, and TRAP, but had minimal effect on procoagulant activity. Most patients receiving dual antiplatelet therapy showed an appropriate reduction in platelet reactivity in response to their treatment; however there was not complete inhibition of increased platelet and EV procoagulant activity in response to ADP, AA, or TRAP. In addition, we could not find any correlation between platelet reactivity and procoagulant activity in patients receiving dual antiplatelet therapy.